Hemothorax as the first manifestation of idiopathic pulmonary arteriovenous malformation - Maja Crkvenac; Marko Jakopovic; Ana Hecimovic; Gordana Pavlisa; Miroslav Samarzija; Andrea Vukic Dugac (Babol University of Medical Sciences, 2018)
Background: Pulmonary arteriovenous malformations (PAVM) are rare pulmonary vascular anomalies and hemothorax as a presenting feature of PAVM is a very rare occurrence. Case presentation: A 45-year old woman presented with chest pain and breathlessness. A chest x-ray showed left-sided pleural effusion. An emergency MSCT scan with contrast showed no signs of pulmonary embolism but instead a probable AV malformation was shown. Diagnostic thoracocentesis revealed hemorrhagic exudate with negative cytology and microbiology findings. Thoracic drainage was performed resulting with complete regression of hemothorax. Three months later, patient was treated with transcatheter embolization of PAVM with good clinical outcome. Conclusions: We have shown that management of PAVM related hemothorax initially by thoracic drainage followed by later on performed catheter embolization of the PAVM could lead to a successful outcome.